Student Worksheets and the Level of Students' Confidence in Solving the Hots Questions - Sukendra, I Komang; Surat, I Made; Widana, I Wayan (Indonesian Research Journal in Education |IRJE|, 2024)
This research aimed to determine whether the group student worksheets method was more effective than the individual student worksheets method in solving questions and whether there was an interaction between the method and the level of student confidence in solving HOTS questions among students. This type of research was experimental research by using a 3x2 factorial treatment design. Liliefors' statistics was used to test normality and Levene's test for homogeneity of variance. All these analyses used the SPSS version 22 program. The results showed the group student worksheets method was more effective than conventional and individual methods in solving the HOTS questions. There was an interaction between the method and the level of confidence in solving HOTS questions which was acceptable. The conclusion is that student worksheets in solving HOTS questions can increase the effectiveness of the self-confidence level of  students.